A Global Research Agenda for Adolescents Living With HIV. (15th August 2018) - Armstrong, Alice; Nagata, Jason M.; Vicari, Marissa; Irvine, Cadi; Cluver, Lucie; Sohn, Annette H.; Ferguson, Jane; Caswell, Georgina; Njenga, Lucy Wanjiku; Oliveras, Carlo; Ross, David; Puthanakit, Thanyawee; et al.
Abstract : Background: Despite growing interest in undertaking research in adolescent HIV, the current pace of interventional research in particular remains very low compared with the needs of adolescents living with HIV (ALHIV). More robust evidence is needed to inform innovative and targeted interventions that bridge research gaps, inform policy, and improve outcomes for adolescents. A global research prioritization exercise was undertaken by WHO and CIPHER to focus efforts on priority research in the context of diminishing resources. Methods: The Child Health and Nutrition Research Initiative (CHNRI) methodology was adapted and used. Outcomes were reviewed by an expert group and 5 priority themes identified for testing, treatment, and service delivery, accounting for existing policies, published literature, and ongoing research. Results: A total of 986 research questions were submitted by 323 individuals from 67 countries. For HIV testing, priority themes included strategies and interventions to improve access, uptake, and linkage to care, and self-testing, particularly for key populations. For treatment, priorities included strategies to monitor and improve adherence, novel drug delivery systems, preventions and management of coinfections, optimal drug sequencing, and short- and long-term outcomes. For service delivery, priorities included service delivery models across the cascade, strategies to improve retention in care and sexual and reproductive health, support for pregnant ALHIV, and the provision of psychosocial support. Conclusions: This prioritized research agenda assists in focusing future research in ALHIV and will help to fill critical knowledge gaps. Key stakeholders, donors, program managers, and researchers should all support these priority questions and themes to collaboratively drive the adolescent HIV research agenda forward. Abstract : Supplemental Digital Content is Available in the Text.